Frequency of Adverse Events Following Q Fever Immunisation in Young Adults - Emily Sellens; Katrina L. Bosward; Susan Willis; Jane Heller; Rowland Cobbold; Jeannette L. Comeau; Jacqueline M. Norris; Navneet K. Dhand; Nicholas Wood (Vaccines, 2018)
Q fever is a zoonosis of concern in many countries. Vaccination is the most effective means of prevention, and since 1989, Australia has had a licensed Q fever vaccine, Q-VAX®. This vaccine was also used in the Netherlands in 2011 following the largest recorded Q fever outbreak globally. There is a paucity of available data regarding adverse events following immunisation (AEFI) for young adult females. Such data are important for informing future vaccination recommendations both within Australia and internationally. This study collected Q fever vaccine (Q-VAX®) AEFI data in veterinary and animal science students at Australian universities. Students were enrolled at the time of vaccination and were emailed a link to an online AEFI survey one week later. Of the 60% (499/827) that responded, 85% were female and the median age was 18 years. Local injection site reactions (ISRs) occurred in 98% (95%; CI 96⁻99%) of respondents, of which 30% (95% CI 24⁻32%) were severe. Systemic AEFI occurred in 60% (95%; CI 55⁻64%) of respondents within the seven days following immunisation. Medical attention was sought by 19/499 (3.8%) respondents, of whom one sought treatment at a hospital emergency department. Females were more likely than males to experience any local ISR (odds ratio [OR] 9.3; 95% CI 2.5⁻33.8; p < 0.001), ISRs of greater severity (OR 2.5; 95% CI 1.5⁻4.2; p < 0.001), and any systemic AEFI (OR 1.9; 95% CI 1.1⁻3.1; p = 0.016). These safety data suggest that a high frequency of adverse events following immunisation should be expected in young adults, particularly females. However, the consequences of Q fever disease are potentially far more debilitating.